Relationship between Glutathione S Transferase P1 and Toll like Receptor 2 Polymorphisms and Infections in Sickle Cell Anemia - Silva, Géssyka Jerônimo; Filho, Romério Alencar de Oliveira; Domingos, Igor de Farias; Santana, Rodrigo Marcionilo de; Batista, Thais Helena Chaves; Araújo, Aderson da Silva; Bezerra, Marcos André Cavalcanti; Filho, José Luiz de Lima; Martins, Danyelly Bruneska Gondim; Araújo, Rosângela Ferreira Frade de (Archives of Clinical and Biomedical Research, 2024)
Infections are the most common complications in individuals with sickle cell anemia. The splenomegaly of these individuals results from erythrocytes being sequestrated, resulting in organ atrophy and fibrosis. However, even before splenomegaly, phagocytic capacity and antibody production are affected as a result of splenic activity, leading to functional asplenia and increased susceptibility to infections. The reactive oxygen species (ROS) produced by phagocytes when activated by pathogenic microorganisms act as bactericides. On the other hand, oxidative damage to erythroid cells also plays a crucial role in hemolysis. We investigated the influence of GSTP1 and TLR2 genetic polymorphisms on susceptibility to infections in 278 patients with sickle cell anemia. These proteins offer protection against oxidative damage and play a key role in host defense against infection, respectively. However, our results do not support any major role of GSTP1 or TLR2 polymorphisms in susceptibility to infection in subjects with sickle cell anemia.